2018
DOI: 10.2174/1568026618666180118153502
|View full text |Cite
|
Sign up to set email alerts
|

ADME and Safety Aspects of Non-cleavable Linkers in Drug Discovery and Development

Abstract: Non-cleavable linkers are used in a number of different modalities for various reasons, such as linking an active drug moiety to half-life extending molecules, to groups that enable a specific tissue or cell targeting or to facilitate active uptake into target cells. Non-cleavable linkers do not have a designated weak point in their structure that can lead to cleavage by proteases, hydrolases or chemically by pH changes. Consequently, when designing a conjugate, the choice of a non-cleavable over a cleavable l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(26 citation statements)
references
References 0 publications
0
26
0
Order By: Relevance
“…In the cytotoxicity test, although the IC 50 value of ionized Cys-15 can be reduced by two orders of magnitude compared to MMAE, we deduced that it is mainly caused by its poorer membrane permeability (MlogP values of Cys-15 and MMAE are −2.093 and 1.191). Generally, the conventional cytotoxicity test cannot effectively reflect its true efficacy in ADC applications [11], which lead to some challenges in designing and screening the ionized cytotoxins of ADCs [35]. Herein, we applied a rapid screening method at the tubulin molecular level and confirmed that the efficacy of Cys-linker-MMAE conjugates did not significantly decrease compared to MMAE.…”
Section: Discussionmentioning
confidence: 69%
See 3 more Smart Citations
“…In the cytotoxicity test, although the IC 50 value of ionized Cys-15 can be reduced by two orders of magnitude compared to MMAE, we deduced that it is mainly caused by its poorer membrane permeability (MlogP values of Cys-15 and MMAE are −2.093 and 1.191). Generally, the conventional cytotoxicity test cannot effectively reflect its true efficacy in ADC applications [11], which lead to some challenges in designing and screening the ionized cytotoxins of ADCs [35]. Herein, we applied a rapid screening method at the tubulin molecular level and confirmed that the efficacy of Cys-linker-MMAE conjugates did not significantly decrease compared to MMAE.…”
Section: Discussionmentioning
confidence: 69%
“…We designed and synthesized a series of linker-MMAE constructs (11)(12)(13)(14)(15) based on different non-cleavable linkers. After these linker-MMAE constructs were modified on the Cys site of the antibodies, the resulting ADCs can be metabolized into stable Cys-linker-MMAE conjugates in the target cells to exert pharmacodynamic effects.…”
Section: Design and Synthesis Of The Cys-linker-mmae-based Adc Payloadsmentioning
confidence: 99%
See 2 more Smart Citations
“…By definition, NC linkers are more stable, but the rate of cargo release cannot be controlled. This strategy relies on the total degradation of the Ab after ADC is internalized and the exposure to lysosomal enzymes . On the other hand, cleavable linkers offer controllable drug release mechanisms, but they display lower systemic stability.…”
Section: Antibody–drug Conjugatesmentioning
confidence: 99%